A key to Begonia section Bracteibegonia from Sumatra with one new species and rediscovery of Begonia fasciculata Jack - Girmansyah, Deden; Hughes, Mark; Jorini, Sulisti; Rugayah, Titik; Chikmawati, Tatik (Phytotaxa, 2020)
Of the 15 species in Begonia sect. Bracteibegonia, 13 are endemic to Sumatra. Following recent fieldwork in North Sumatra, Begonia fasciculata Jack has been observed for the first time since it’s description in 1822 and is neotypified. A new species in B. sect. Bracteibegonia from the Mentawai Islands is described, and a key to all species in the section from Sumatra is provided.